Kuadratik Programlama Yöntemiyle Markov Geçiş Matris Değerlerinin Belirlenmesi - (:unkn) unknown (My University, 2007)
Modern olasılık teorisi geçmiş verilerin bilinmesi ile geleceği tahmin etmede şans süreçlerini kullanır. Şansa dayalı deneylerin bir dizisini gözlemlediğimizde geçmiş verilerin hepsi gelecek deneyler için tahminimizi etkileyebilir. 1907 de A;A Markov şans süreçlerinin önemli yeni bir tipi üzerinde çalışmaya başladı. Markov zincirleri olarak adlandırılan bu süreçte yapılan bir deneyin sonucu bir sonraki deneyin sonucunu etkileyebilir. Bir sistemin (Markov modelinin) yapılandırılmasında süreç içerisinde belirlenmesi gereken iki unsur vardır. Bu unsurlar sistemin mümkün durumlarını ve durumlar arasında hareketin geçiş olasılıklarının belirlenmesini içerir. Markov zincirleri stokastik süreçler olarak bilinen daha genel olasılık modellerinin özel bir durumudur ve sistemin gelecek yörüngesinin sadece şu anki mevcut duruma bağlı olduğunu yani geçmiş tüm durumlardan bağımsız olduğunu vurgular. Bu makalede geçiş matrisi Kuadratik Programlama ile belirlenmektedir.

Modern probability theory studies chance, processes for which the knowledge of previous outcomes influences predictions for future experiments. In principle, when we observe a sequence of chance experiments, all of the past outcomes could influence our predictions for the next experiments. In 1907, A. A. Markov began the study of an important new type of chance process. In the process, the outcome of a giyen experiment can affect the outcome of the next experiment. This type of process is called a Markov Chain. There are two elements that must be determined in the process of constructing a Markov model of a system. These elements include determining the possible states of the system and the transition probabilities of moving between states. : Markov chains are a special case of the more general probabilistic models known as stochastic processes. Markov chains are stochastic processes without . after-effect, that is, such processes for which the knowledge of the present state uniquely determines its future stochastic behaviour, and this behaviour does not depend on the past of the process. In this paper transition matrix is determined with Quadratic Programming.
Keywords: İktisat; İşletme